Perceived sexual dysfunction and factors attributed by women with leprosy - Sacha Frota Nogueira, Paula; Farias da Rocha, Ana Carolina; Corrêa dos Santos, Stefanny (O Mundo da Saúde, 2022)
Leprosy is an infectious disease of slow evolution, high infectivity and low pathogenicity, which presents dermato-neurological signs and symptoms. The change in the sexual pattern caused by female sexual dysfunction is a complication that can be experienced by women with leprosy, causing a negative impact on quality of life. The objective of this study was to identify the perceived sexual function and factors attributed by women with leprosy. This descriptive, cross-sectional study was carried out in two dermatology outpatient clinics in the city of Fortaleza, Ceará, with 76 women with leprosy. An interview form was used with socioeconomic and clinical variables, and application of the Female Sexual Function Index. Young adulthood prevailed, with unfavorable socioeconomic conditions, and multibacillary forms. The perception of sexual dysfunction was predominant among the interviewees (60.5%), who cited as factors related to self-image (26.0%) and changes in sexual desire (26.0%). The domains with the greatest change were: satisfaction (R=3.06), arousal (R=3.78), desire (R=3.79), and orgasm (R=3.79). The approach to the sexual function of women with leprosy should be carried out by health professionals, in order to promote greater sexual and personal satisfaction for the patient.